2011
DOI: 10.1021/ic1024185
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Dinuclear Copper(II) Complexes of a Hydroxybenzamide Ligand with Diimine Coligands: the 5,6-dmp Ligand Enhances DNA Binding and Cleavage and Induces Apoptosis

Abstract: The dinuclear copper(II) complexes [Cu(2)(LH)(2)(diimine)(2)(ClO(4))(2)](ClO(4))(2) (1-4), where LH = 2-hydroxy-N-[2-(methylamino)ethyl]benzamide and diimine = 2,2'-bipyridine (bpy; 1), 1,10-phenanthroline (phen; 2), 5,6-dimethyl-1,10-phenanthroline (5,6-dmp; 3), and dipyrido[3,2-d:2',3'-f]quinoxaline (dpq; 4), have been isolated and characterized. The X-ray crystal structure of complex 1 contains two copper(II) centers bridged by the phenolate moiety of the amide ligand. All of the complexes display a ligand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(88 citation statements)
references
References 84 publications
9
79
0
Order By: Relevance
“…Several copper complexes have been found to exhibit these modes of interaction. Furthermore, a number of the copper complexes have been found to exhibit cytotoxicity levels that are comparable to or greater than that of cisplatin [26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Several copper complexes have been found to exhibit these modes of interaction. Furthermore, a number of the copper complexes have been found to exhibit cytotoxicity levels that are comparable to or greater than that of cisplatin [26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The hypochromism is 45.83 % with red shift of 3 nm and 26.32 % with red shift of 2 nm for compounds 3 and 4, respectively. Hypochromism is caused by the strong interaction between compounds and CT DNA base pairs (Ramakrishnan et al 2011). These characteristics indicate that two compounds interact with DNA most likely through a mode that involves a stacking interaction between the aromatic chromophore and the base pairs of DNA.…”
Section: Electronic Absorption Spectramentioning
confidence: 99%
“…[22,23]. Many copper (II) complexes with biological activities such as antibacterial, anti-cancer and cancer inhibiting properties have already been dealt with in the literature [24,25]. Palaniandavar and co-workers have reported that copper (II) complexes are the best alternatives to cisplatin because copper plays many significant parts in biological systems and is a biocompatible metal [26], considering the strong interactions of copper complexes with DNA through surface associations or intercalation [27].…”
Section: Introductionmentioning
confidence: 99%